30 years of study of Kingella kingae: post tenebras, lux. (February 2013) - Ceroni, Dimitri; Dubois-Ferrière, Victor; Cherkaoui, Abdessalam; Lamah, Léopold; Renzi, Gesuele; Lascombes, Pierre; Wilson, Belaieff; Schrenzel, Jacques
Kingella kingae is a Gram-negative bacterium that is today recognized as the major cause of joint and bone infections in young children. This microorganism is a member of the normal flora of the oropharynx, and the carriage rate among children under 4 years of age is approximately 10%. K. kingae is transmitted from child to child through close personal contact. Key virulence factors of K. kingae include expression of type IV pili, Knh-mediated adhesive activity and production of a potent RTX toxin. The clinical presentation of K. kingae invasive infection is often subtle and may be associated to mild-to-moderate biologic inflammatory responses, highlighting the importance a high index of suspicion. Molecular diagnosis of K. kingae infections by nucleic acid amplification techniques enables identification of this fastidious microorganism. Invasive infections typically respond favorably to medical treatment, with the exception of cases of endocarditis, which may require urgent valve replacement.